2021
DOI: 10.1002/aelm.202100891
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐Inspired Adaptive Sensing through Electropolymerization of Organic Electrochemical Transistors

Abstract: for converting ionic signals into electronic ones thanks to the unique property of organic mixed ionic-electronic conductors (OMIECs). [4] Ionic concentration from an analyte or ionic currents from electroactive cells can be efficiently sensed/probed and amplified, thus making OECTs attractive sensors. [5] In the perspective of neuromorphic engineering, the same devices are capitalizing on the possibility to engineer devices where ion-electron coupling can be used to implement various synaptic plasticities, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Other than the spin coating technique used in the studies mentioned above, electropolymerization is one major method of fabricating OECT devices. [108][109][110][111][112] The electropolymerization of 3,4-ethylenedioxythiophene (EDOT) monomer originated in early studies in conductive polymers [113][114][115] and has continued to be used as an effective method to obtain polymer films in a position-selective way, including forming dendric conductive networks. 109,110 In addition, modified EDOT derivatives (Fig.…”
Section: Organic Electrochemical Transistorsmentioning
confidence: 99%
“…Other than the spin coating technique used in the studies mentioned above, electropolymerization is one major method of fabricating OECT devices. [108][109][110][111][112] The electropolymerization of 3,4-ethylenedioxythiophene (EDOT) monomer originated in early studies in conductive polymers [113][114][115] and has continued to be used as an effective method to obtain polymer films in a position-selective way, including forming dendric conductive networks. 109,110 In addition, modified EDOT derivatives (Fig.…”
Section: Organic Electrochemical Transistorsmentioning
confidence: 99%
“…Essentially, the OECT operates via ion injection (usually using an electrochemical bias application) from an electrolyte solution toward the channel based on an OMIEC material leading to a change in the oxidation state of the conjugated polymer and thus altering the electronic transport. Efforts to unravel mixed ionic-electronic transport mechanisms have been addressed by computational simulation studies, where most frequently, ionic and electronic transport are treated separately, i.e., ionic transport is computed in large polymeric systems using classical molecular dynamics , and electronic transport is computed in smaller oligomeric systems using first-principles calculations . However, recent literature has just addressed mixed ionic-electronic transport mechanisms simultaneously and other studies have also provided interesting insights on swelling and ionic injection processes for OMIEC channel materials comprising OECT devices. Experimentally, insights on mixed ionic-electronic transport mechanisms in OMIECs based on impedance spectroscopy studies have been addressed separately, i.e., in the in-plane configuration for OMIECs , and in the out-of-plane configuration for OMIECs comprising OECT devices. The use of impedance spectroscopy has also been a key to boosting frequency-dependent transconductance experiments relevant to bioelectronic applications. In addition, some recent studies are being focused on establishing a link between structural and mixed ionic-electronic transport properties based on the characterization of OMIEC materials under operation conditions in OECT devices . For instance, X-ray and neutron reflectivity studies on PEDOT:PSS have revealed that the swelling-driven microscopic rearrangement of the conducting PEDOT-rich cores in the PSS matrix strongly influences the electrical charge transport. , A recent study performed by a combination of electrochemical quartz microbalance, X-ray scattering, and spectrochemical techniques has shown that infiltration of the hydrated dopant ions into the OMIEC material irreversibly changes the polymer structure and negatively impacts the efficiency, reversibility, and speed of charge generation .…”
Section: Introductionmentioning
confidence: 99%
“…[ 37,38 ] The unique ion‐mediated conductance modulation makes it ideal for mimicking the neurotransmitter‐mediated synaptic weight modulation because ions are also the carrier in brain neuro functions. [ 39–44 ] EGTs with various types of electrolytes were studied for mimicking synaptic metaplasticity behaviors. John et al.…”
Section: Introductionmentioning
confidence: 99%
“…[37,38] The unique ion-mediated conductance modulation makes it ideal for mimicking the neurotransmittermediated synaptic weight modulation because ions are also the carrier in brain neuro functions. [39][40][41][42][43][44] EGTs with various types of electrolytes were studied for mimicking synaptic metaplasticity behaviors. John et al emulated homeostatic synaptic metaplasticity behaviors on 2D transition metal di-chalcogenide (MoS 2 ) transistors gated with ion liquids.…”
mentioning
confidence: 99%